Peningkatan Hasil Belajar Pendidikan Pancasila Peserta Didik pada Materi Identitas Diri Menggunakan Model Cooperative Tipe Team Games Tournament di Kelas IV SD Negeri 12 Bukit Cangang Kota Bukittinggi - Annisa, Khairatun; Desyandri, Desyandri (Darul Yasin Al Sys, 2025)
The research was motivated by observations and interviews conducted by researchers at SD Negeri 12 Bukit Cangang Bukittinggi City. During the observation, the researcher found that the learning outcomes of students in the elementary school were still relatively low with educator-centered learning, the methods used were monotonous, the low level of participation of students in the learning process and the planning prepared by educators was not optimal. The purpose of this study was to describe the improvement of planning, implementation and student learning outcomes through the use of the Team Game Tournament type Cooperative model at SD Negeri 12 Bukit Cangang Bukittinggi City. This research is a classroom action research (PTK) that uses qualitative and quantitative approaches. This research was conducted in two cycles. The results showed an increase in: a) Teaching module cycle I with an average of 84.25% (good) and cycle II 93.7% (very good), b) Implementation in the aspect of educators cycle I with an average of 87.8% (good) and cycle II 95.2% (very good), while in the aspect of students cycle I with an average of 85.4% (good) and cycle II 95.2% (very good), c) Assessment of students in improving learning outcomes in cycle I obtained an average of 80.7 and cycle II with an average of 87.7. Based on these results it can be concluded that the Cooperative model of Team Game Tournament type can improve the learning outcomes of students in learning Pancasila Education. Future research could explore effective time management strategies in implementing game-based learning models to better align with formal learning schedules.